Perceptions of second year psychology students at the University of Limpopo towards sexually transmitted infection (STI) testing - Mahasha, Tebogo (My University, 2022)
Sexually transmitted infections (STIs) remain a serious global health challenge, which if left untreated, may threaten an individual’s health. The challenge regarding the prevention of STI transmission is the asymptomatic nature of STIs during their early stages. Hence, STI testing is vital in tackling the devastating impact of STIs. The Health Belief Model (HBM) provided a lens through which to understand the study as it provides a basis upon which to predict health behaviours. The study employed a qualitative research method. The study aimed to explore University of Limpopo students’ perceptions towards STI testing. The objectives of the study were (1) to establish the perceptions of second-year Psychology students at the University of Limpopo towards STI testing, and (2) to determine the importance of testing for STIs among second-year Psychology students at the University of Limpopo. The study purposively sampled 15 second-year Psychology students at the University of Limpopo. It was found that the participants were knowledgeable about STI testing. The study revealed psychological effects associated with STI testing ranging from anxiety-related attacks, stress, depression, and insomnia, among others. It further revealed important aspects learned about STI testing, i.e. that some STIs are curable, early detection facilitate early treatment, and STIs are not a myth. The importance of STI testing was also determined. It was also noted that it is important to know one’s health status to prevent mother-to-child transmission and health consequences. The study further established the experiences of STI testing, such as anxiety, stress, feeling embarrassed, ashamed, and overwhelmed. In addition, it was found that students are reluctant to test for STIs because of low-risk perception of contracting STIs, the fear of receiving positive test results, lack of knowledge, stigma, and the judgemental attitude of health professionals. The findings also revealed that students consider testing to be a good health behaviour, although the majority of them rarely consult for STI testing. Constructive counselling is highly recommended for those who consult for STI testing. It is further recommended that future research should be conducted in other universities with broader sample size.
Thesis (M.A. (Clinical Psychology)) -- University of Limpopo, 2022
Keywords: Perceptions; Sexually Transmitted infection (STI); Health Belief Model (HBM); Sexually transmitted diseases -- Psychological aspects; College students -- South Africa -- Psychology; Psychology students; Sexually transmitted diseases -- Testing